How reduced excitonic coupling enhances light harvesting in the main photosynthetic antennae of diatoms - Krüger, Tjaart P J; Malý, Pavel; Alexandre, Maxime T A; Mančal, Tomáš; Büchel, Claudia; van Grondelle, Rienk (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Strong excitonic interactions are a key design strategy in photosynthetic light harvesting, expanding the spectral cross-section for light absorption and creating considerably faster and more robust excitation energy transfer. These molecular excitons are a direct result of exceptionally densely packed pigments in photosynthetic proteins. The main light-harvesting complexes of diatoms, known as fucoxanthin-chlorophyll proteins (FCPs), are an exception, displaying surprisingly weak excitonic coupling between their chlorophyll (Chl) a's, despite a high pigment density. Here, we show, using single-molecule spectroscopy, that the FCP complexes of Cyclotella meneghiniana switch frequently into stable, strongly emissive states shifted 4-10 nm toward the red. A few percent of isolated FCPa complexes and ∼20% of isolated FCPb complexes, on average, were observed to populate these previously unobserved states, percentages that agree with the steady-state fluorescence spectra of FCP ensembles. Thus, the complexes use their enhanced sensitivity to static disorder to increase their light-harvesting capability in a number of ways. A disordered exciton model based on the structure of the main plant light-harvesting complex explains the red-shifted emission by strong localization of the excitation energy on a single Chl a pigment in the terminal emitter domain due to very specific pigment orientations. We suggest that the specific construction of FCP gives the complex a unique strategy to ensure that its light-harvesting function remains robust in the fluctuating protein environment despite limited excitonic interactions.
Keywords: Light-Harvesting Protein Complexes; Photosynthesis; světlosběrné proteinové komplexy; photosynthetic excitons; single-molecule spectroscopy; Diatoms; fucoxanthin–chlorophyll protein; fotosyntéza; protein disorder; rozsivky; light-harvesting complex